2021
DOI: 10.1371/journal.pone.0251410
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on the clinical trial

Abstract: The objective of this study was to explore the impact of the coronavirus disease 2019 epidemic on ongoing and upcoming drug clinical trials. Qualitative semi-structured interviews were conducted with clinical trial staff and clinical trial subjects were surveyed by questionnaire in this study. The results of interviews and questionnaire showed that coronavirus disease 2019 pandemic has led to many changes in the implementation of drug clinical trials, including: a variety of meetings being held online webinars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 10 publications
3
26
0
Order By: Relevance
“…In the opposite side, most of the studies have focused on the benefits of telemedicine strategies for COVID-19, however, potentially disadvantages and limitations must be in-depth discussed, eg. [32] revealed that 82.6% on a sample of 115 medical residents feel less confident of treating chronic disease patients using telemedicine therefore understanding these in-depth limitations will be suitable. The following study was focused on primary health care, therefor a study that covers secondary medical care will be suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the opposite side, most of the studies have focused on the benefits of telemedicine strategies for COVID-19, however, potentially disadvantages and limitations must be in-depth discussed, eg. [32] revealed that 82.6% on a sample of 115 medical residents feel less confident of treating chronic disease patients using telemedicine therefore understanding these in-depth limitations will be suitable. The following study was focused on primary health care, therefor a study that covers secondary medical care will be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on telemedicine during the COVID-19 pandemic have focused on applications that include, forward triage [12], automated logic flows (bots) [12], management of chronic conditions [13], mental health services [14], palliative care [15] and teleneurology [16]; challenges, that include, coordination and integration of involved sectors [12,17,18], creation of regulatory frameworks [4,13,[17][18][19], accessibility to mobile technologies [20]; reviews [21,22]; suggestions of a Software-Defined Network architecture for telemedicine purposes [23]; suggestions on potential benefits of using telemedicine for vulnerable groups that do not have access to clinical services due to COVID-19, such as gestant women from developing countries, as pregnancy has been reported as a clinical condition with risk factors [24,25]; discussions on the legislation of telemedicine as its adoption has become increasingly widespread and new legislation frameworks will need to be developed to satisfy this new demand [26]; discussions about lessons of operationalizing telemedicine in ophthalmology and its potential effect for health systems [27,28]; propositions of models of clinical attention that consisted in a mix of in-person visits with telemedicine support [29]; discussions of solutions for long-term COVID-19 consequences that can include telemedicine support [30]; propositions of offering telehealth service in public spaces as a form to prevent the intimated partner violence (IPV), as it has been reported that this situation has been increased during the pandemic COVID-19 due to the process of lockdown [31]; studies of the impact of COVID-19 of clinical trials which concluded that the pandemic has damaged the quality of the studies [32].…”
Section: Plos Onementioning
confidence: 99%
“…As happened in other clinical contexts [33] , [34] , also in particle RT the clinical research had to readapt to the contingent situation preferring, according to the national and international oncological recommendations, short schedules of medical and RT treatments. Considering the prolonged pandemic, the “new normality” should consider in all studies contingency plans and ethical amendments [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Non-COVID-19 trials permitted to continue or resume and required substantial adjustments to recruitment, intervention, data collection and trial management protocols in response to the social distancing and quarantine challenges posed by COVID-19 [6,7]. Recent systematic reviews and studies have reported that these mitigation efforts have resulted in enrolment delays and operational gaps that have negatively impacted on trial timelines and outcomes [8,9].…”
Section: Introductionmentioning
confidence: 99%